EFEK EVALUASI KINERJA ELEKTRONIK PADA KINERJA KARYAWAN SELAMA SISTEM DALAM JARINGAN DI MASA PANDEMI COVID-19 DENGAN PERAN BURNOUT SEBAGAI VARIABEL INTERVENING (Studi Pada Aparatur Sipil Negara Sekretariat Daerah Kota Semarang) - Griselda Malora; Edy Raharja (Diponegoro Journal of Management, 2022)
This research aims to analyze the effect of e-evaluation variabel on employee performance through burnout as an intervention variabel at the Sekretariat Daerah Kota Semarang. This research uses questionnaire distribution research and studies using journal, books, and company data. The population used is ASN who are actively working at Sekretariat Daerah Kota Semarang. The data collection method used is the distribution of questionnaires using random sampling method. Analysis of research data using SmartPLS applications with the method of Structural Equation Modeling (SEM). The data analysis used is descriptive index, reliability test, validity test, outer model, inner model, hypothesis testing, and intervention test. The test analysis in this study shows that the e-evaluation variable has a significant positive effect on employee performance. The e-evaluation had a negative significant effect to burnout. In addition, it is also known that there is a negative significant influence between burnout and employee performance.